2019
DOI: 10.3847/1538-4357/ab04aa
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Dynamics and Varying Plasma Emission in Large-scale Coronal Loops

Abstract: In this study we report detailed observations of magnetic environment at four footpoints of two warm coronal loops observed on 5 May 2016 in NOAA AR 12542 (Loop I) and17 Dec 2015 in NOAA AR 12470 (Loop II). These loops were connecting a plage region with sunspot periphery (Loop I) and a sunspot umbra (Loop II). We used Solar Dynamics Observatory (SDO) and Goode Solar Telescope (GST) data to describe the phenomenon and understand its causes. The study indicates loop brightening episodes were associated with mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Watanabe et al 2011;Vissers et al 2013;Peter et al 2014;Kim et al 2015;Vissers et al 2015;Rutten et al 2015;Rezaei & Beck 2015;Nelson et al 2016;Tian et al 2016;Reid et al 2016;Rutten 2016;Nelson et al 2017;Toriumi et al 2017;Hong et al 2017;Libbrecht et al 2017;van der Voort et al 2017;Tian et al 2018;Ulyanov et al 2019;Huang et al 2019;Chen et al 2019). In addition to the above energy bursts and plasma ejections, recent observations have suggested that the cancellation of opposite polarities at the footpoints of coronal loops could be responsible for the brightening of coronal loops (Tiwari et al 2014;Chitta et al 2017b;Huang et al 2018;Chitta et al 2018;Şahin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe et al 2011;Vissers et al 2013;Peter et al 2014;Kim et al 2015;Vissers et al 2015;Rutten et al 2015;Rezaei & Beck 2015;Nelson et al 2016;Tian et al 2016;Reid et al 2016;Rutten 2016;Nelson et al 2017;Toriumi et al 2017;Hong et al 2017;Libbrecht et al 2017;van der Voort et al 2017;Tian et al 2018;Ulyanov et al 2019;Huang et al 2019;Chen et al 2019). In addition to the above energy bursts and plasma ejections, recent observations have suggested that the cancellation of opposite polarities at the footpoints of coronal loops could be responsible for the brightening of coronal loops (Tiwari et al 2014;Chitta et al 2017b;Huang et al 2018;Chitta et al 2018;Şahin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Multiwavelength analysis is a widely used method in solar physics research. The community increasingly praises coordinated observations involving multiple instruments, allowing us to construct a comprehensive picture of a solar event (e.g., Ji et al 2012;Şahin et al 2019;Samanta et al 2019). Well-organized campaign observations among multiple space-and groundbased telescopes are playing an important role in solar physics studies.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from bursts and jets, observations have suggested that the cancellation of opposite polarities at the footpoints of coronal loops could be responsible for the brightening of coronal loops (Tiwari et al 2014;Chitta et al 2017Chitta et al , 2018Huang et al 2018;Şahin et al 2019). Potentially, even spicules could be linked to flux cancellation Samanta et al 2019).…”
Section: Introductionmentioning
confidence: 99%